Differentiated supervision : growing teachers and getting results - Mausbach, Ann T.; Morrison, Kimberly (Thousand Oaks: Corwin press, 2023)
"This book introduces a framework for helping leaders differentiate supervision practices and presents a comprehensive model that provides a coherent method for supporting individuals, small groups, and the whole school in implementing high leverage strategies that improve student learning"--
Differentiated supervision 101 -- Element I : universal support with qualitative feedback -- Element II : individual/small group support with qualitative feedback -- Element III : universal support with quantitative feedback -- Element IV : individual support with quantitative feedback -- Leading the differentiated supervision model.
Includes bibliographical references and index.
Keywords: School supervision; School personnel management; Teacher effectiveness; Feedback (Psychology)